Factors contributing to and detracting from relational trust in leadership: The case of primary schools in South Africa - Baxter, Jacqueline; Ehren, Melanie (Frontiers in Education, 2023)
Trust in leadership is a key element in organisational effectiveness and the foundations of a successful school. However, this element of leadership is underexplored in terms of empirical work, concomitantly, distrusting school cultures have been identified as inhibitors of school improvement. This paper explores trust in leadership through a relationship-based perspective of trust, taking by taking the case of 8 primary schools, in South Africa, to examine: Which factors positively influence trust in leadership of primary schools and which undermine it. The paper begins by conceptualising trust and relational based trust in leadership before moving on to analyse trust in educational settings. It explores trust between leaders and staff and within staff member groups . From there the paper discusses the implications of the findings within the particular cultural context of South Africa. The paper concludes with a summary of factors detracting from and contributing to trust in leadership, and to what extent these align with relational trust in leadership and the construction of effective learning communities. In so doing, the paper raises awareness of the importance of trust in leadership in the context of South African Primary Education and how it can undermine leadership if not established throughout relationships in schools, offering insights for primary leaders working within the African context. It also questions the appropriateness of adopting a relational understanding of trust in distributed leadership in relation to this particular context.